Fundamentals of human resource management (McGraw-Hill, 2010)
As competitors strive to win the war for talent, effective human resource management is necessary to gain true competitive advantage in the marketplace. Three challenges companies face are sustainability, technology, and globalization. Human Resource Management 7th Edition brings these challenges to life by highlighting real-world examples pertaining to these issues and relating it to the concepts within the chapter. This best-selling McGraw-Hill/Irwin Human Resource Management title provides students with the technical background needed to be a knowledgeable consumer of human resource (HR) products and services, to manage HR effectively, or to be a successful HR professional. While clearly strategic in nature, the text also emphasizes how managers can more effectively acquire, develop, compensate, and manage the internal and external environment that relates to the management of human resources.